Thrombocytopenia in high‐risk patients with antiphospholipid syndrome. (25th January 2018) - Pontara, E.; Banzato, A.; Bison, E.; Cattini, M. G.; Baroni, G.; Denas, G.; Calligaro, A.; Marson, P.; Tison, T.; Ruffatti, A.; Pengo, V.
Abstract : Essentials The prevalence of thrombocytopenia in patients with antiphospholipid syndrome is not well defined. We studied triple positive patients with antiphospholipid syndrome and its catastrophic variant. Prevalence of thrombocytopenia was 6% and 100% in patients who developed the catastrophic form. In triple positive patients thrombocytopenia is low and platelets drop during the catastrophic form. Summary: Background: Thrombocytopenia is the most common non‐criteria hematological feature in patients with antiphospholipid syndrome (APS). This condition is more common in patients with catastrophic APS (CAPS). Objectives: To evaluate the prevalence of thrombocytopenia in a large series of high‐risk patients with APS, and to assess the behavior of the platelet count during CAPS. Methods/Patients: This was a cross‐sectional study in which we analyzed the platelet counts of a homogeneous group of high‐risk APS patients (triple‐positive). Six of these patients developed a catastrophic phase of the disease, and the platelet count was recorded before the acute phase, during the acute phase, and at recovery. Results: The mean platelet count in 119 high‐risk triple‐positive patients was 210 × 10 9 L −1 . With a cut‐off value for thrombocytopenia of 100 × 10 9 L −1, the prevalence of thrombocytopenia was 6% (seven patients). No difference between primary APS and secondary APS was found. In patients who suffered from CAPS, a significant decrease from the basal count (212 ± 51 × 10 9 L −1 ) to that at the time of diagnosis (60 ± 33 × 10 9 L −1 ) was observed. The platelet count became normal again at the time of complete remission (220 ± 57 × 10 9 L −1 ). A decrease in platelet count always preceded the full clinical picture. Conclusions: This study shows that, in high‐risk APS patients, the prevalence of thrombocytopenia is low. A decrease in platelet count was observed in all of the patients who developed the catastrophic form of the disease. A decrease in platelet count in high‐risk APS patients should be considered a warning signal for disease progression to CAPS.